Disgorgement of Profits: An Alternative Solution to Stolen State Assets’ Recovery from Corporate Financial Crimes - Ariyanny, Renny; Bae, Sung-jun; Dermawan, Mohammad Kemal (Faculty of Law, Hasanuddin University, 2023)
In recent years, the Indonesian government has suffered a huge loss of state assets due to the misbehavior of corporations in financial management because the Indonesian legal system does not have a specific regulation to address corporate financial crime. When a corporate financial crime case arises, Indonesian law enforcement approaches this crime using the Anti-Corruption Act. However, the aim to retrieve the stolen government assets purloined by a corporation using the Anti-Corruption Act is still insufficient, therefore, other related regulations such as the Money Laundering Act have to apply as an additional instrument to realize optimal recovery from the misbehaving corporation. Because the long process involved in criminal and civil courts it is sometimes a waste of the law enforcement effort and the funds expended to get paid back from offenders and/or corporations because the money received is much lower than the money lost or even zero. To bridge the gap between the money lost initially and the repayment money, because of the lack of special legal regulation concerning corporate financial crime, this research intends to study the possibility of using a “disgorgement of profits” approach as a faster way to get the maximum repayment of stolen money/assets from instances of corporate financial crime in out-of-court settlements.